Nilai-nilai Karakter Dalam Pendidikan Kepramukaan Di MI Mambaul Ulum Dagan Solokuro Lamongan - Wadud Nafii’ul Umam, Abd.; Rohmah, Nafilatur (MADINAH, 2022)
The aims of this study are: (1) to find out the character values in scouting education at MI Mambaul Ulum Dagan Solokuro Lamongan; (2) knowing the factors supporting and inhibiting the cultivation of character values in scouting education at MI Mambaul Ulum Dagan Solokuro Lamongan. The research uses a qualitative approach with case study analysis. Data collection techniques through observation, interviews, and documentation studies. Data analysis techniques through data reduction, data presentation, and verification. Checking the validity of the data through technical triangulation and source triangulation. The results of this study are: (1) character values in scouting education consist of religious character values, character values related to oneself such as independence, creativity, and discipline, and character values related to others and the environment. (2) supporting factors for inculcating character values in scouting education are having loyal coaches, good cooperation from institutions and parents in scout extracurricular activities, complete facilities ranging from fields and outdoors to scouting tools and scout studios all of them are supportive, and the awareness and interest of student to take extracurricular activities is very high. The inhibiting factor is that the scout members are busy when delivering scouting material so that disrupts the activity process, some students need special attention due to certain conditions, the implementation of scouts is closed during school exams so that scouting activities must stop in a few days.